On comparison of estimation techniques for solar radiation missing data at Alor Setar and Penang area in northern peninsular Malaysia - Zainudin, Mohd Lutfi; Saaban, Azizan; Abu Bakar, Mohd Nazari (Pushpa Publishing House, 2016)
The radiation data is important for solar data analysis which is significantly for modeling, designing on energy conversion system development and outputting it as a variable that is needed by other related scientific researches.Obtaining the complete data for solar intensity is a tough job when the technical problem is raised either from the sensor’s devices or faulty data transmission. Next, missing values occur accordingly.As a solution, missing value estimation has been introduced to substitute the absent values with imputed values.This article is highlighted to propose cubic Bézier interpolation as potential techniques to generate replacement values. Afterwards, compare the performance capability of few submitted interpolation techniques dealing with difference amount of simulated missing data. Based on our knowledge, curiosity works for replaceable values by applying Bézier interpolation on solar radiation data is limited. The cubic Bézier interpolation performs very well on both areas but the most effective condition is at the lower missing values and higher absent values that come from Alor Setar and Penang cities, respectively, which offer the lowest RMSE value and the r² value nearest to 1